Conductivities of Graphite Fiber Composites with Single-Walled Carbon Nanotube Layers - Yoo, Lawrence; Kim, Hansang (KOREAN SOC PRECISION ENG, 2011)
The present study investigates the potential of air-spraying method in enhancement of electrical and thermal conductivities. Single-walled carbon nanotubes (SWCNTs) functionalized with carboxylic acid groups were air-sprayed on the surface of carbon fiber prepreg. The prepregs were stacked up and processed to carbon fiber laminates with SWCNTs layered between plies. From scanning electron microscopy, it was discovered that SWCNTs formed thin bands between carbon fiber layers and did not transport deep into the thickness direction due to low resin flow during cure. As it was hypothesized prior to experiments, the electrical conductivity was significantly enhanced by using a higher concentration of SWCNTs, while no amelioration for thermal conductivity was observed.
Keywords: EPOXY COMPOSITES; THERMAL-CONDUCTIVITY; ELECTRICAL-CONDUCTIVITY